Predictive model for self-reliance intention of Malaysian Polytechnic Students - Ibrahim, Mohammed (2019)
Self-reliance intention signifies the actual self-reliance behaviour of students. However, the magnitude of the influence of predicting factors towards self-reliance is not empirically known. The research aimed to investigate the extent to which predicting factors could influence self-reliance intentions and develop a model to predict self-reliance among polytechniv students. The research used quantitative context and employed correlation research design. The tool used for data collection was a set of questionnaires, administered to the final year students of conventional polytechnics in five zones: East Malaysia, central, east, north and south of Malaysia. A total of 650 final year students were selected from these polytechnics. Partial Least Squares Structural Equation (PLS-SEM) were used in the data analysis. Results revealed that perception on the TVET program, technical tendency and economic support, influence self-reliance intention and these factors influences collectively predicted 42 per cent of the students’ self-reliance intention. However, the school physical environment support and social support were not found to influence self-reliance intention. The mediation results further revealed that technical tendency has a significant mediation effect on self-reliance intention, social support, physical environmental, economic support and perception on the TVET program. The technical tendency mediation effects predict 48 per cent on self-reliance intention. Social support and physical environment were fully mediated between the mediator and self-reliance intention. The research provides empirical evidence of the significant influence of the research predictive factors toward self-reliance intention. The findings suggest that a combination of theories could be employed to develop a model and the research result could practically be used for curriculum planning in Malaysian polytechnics.